2013
DOI: 10.3390/vaccines1030328
|View full text |Cite
|
Sign up to set email alerts
|

Isotype Diversification of IgG Antibodies to HIV Gag Proteins as a Therapeutic Vaccination Strategy for HIV Infection

Abstract: The development of vaccines to treat and prevent human immunodeficiency virus (HIV) infection has been hampered by an incomplete understanding of “protective” immune responses against HIV. Natural control of HIV-1 infection is associated with T-cell responses against HIV-1 Gag proteins, particularly CD8+ T-cell responses restricted by “protective” HLA-B alleles, but other immune responses also contribute to immune control. These immune responses appear to include IgG antibodies to HIV-1 Gag proteins, interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 96 publications
(123 reference statements)
4
24
0
Order By: Relevance
“…Numerous studies have demonstrated that higher serum/plasma levels or avidity of IgG antibodies against HIV-1 Gag proteins are associated with slower progression of HIV disease (reviewed in (11)). However, to our knowledge, this is the first study to show an association between the functional activity of an IgG antibody response against HIV Gag proteins and natural control of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that higher serum/plasma levels or avidity of IgG antibodies against HIV-1 Gag proteins are associated with slower progression of HIV disease (reviewed in (11)). However, to our knowledge, this is the first study to show an association between the functional activity of an IgG antibody response against HIV Gag proteins and natural control of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in simian-human immunodeficiency virus (SHIV)-infected macaques have shown that human monoclonal antibodies against HIV-1 Env antigens suppress replication of SHIV and are capable of inducing long-term suppression of SHIV infection in a subset of animals (9, 10). Numerous studies have also demonstrated that IgG antibodies against HIV-1 Gag proteins are associated with slower progression of HIV disease (reviewed in (11)) but it is unclear what role, if any, these antibodies play in controlling HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have associated slower disease progression with higher serum levels of HIV-1 Gag-specific IgG antibodies [reviewed in (24)]. We next, hypothesized that Tfh1 responses impact SPVL by driving the production of HIV-specific IgG antibodies.…”
Section: Resultsmentioning
confidence: 98%
“…This increase may be due to class switching which induces IgG subclasses. Several cytokines have been reported to specifically induce each IgG subclass . For example, IgG3 is induced by interferon (IFN)‐γ .…”
Section: Discussionmentioning
confidence: 99%